2024
DOI: 10.1021/acs.oprd.3c00515
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Circulation Flow Platform Facilitating Practical Large-Scale Heterogeneous Photocatalysis

Chenguang Liu,
Lei Song,
Qiong Liu
et al.

Abstract: Although continuous flow synthesis using microtubing reactors has provided a wealth of opportunities for homogeneous photochemical synthesis and has proven particularly beneficial in scaling up processes, employing continuous flow technology to scale up heterogeneous photoreactions is challenging due to the issues including handling of solids, poor light penetration, and commonly lengthy reaction time. Here we present a solution to these issues by changing the continuous flow mode to a high-speed circulation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(68 reference statements)
1
2
0
Order By: Relevance
“…To showcase the practicality of this method, we conducted a two-step gram-scale synthesis of anti-inflammatory drug nabumetone from commercially available 2-ethynyl-6-methoxynaphthalene ( 7w ) using our reductive hydrocarboxylation reaction. Given the poor solubility of oxalates in MeCN, a simple high-speed circulation flow was employed to scale up the photocatalytic reductive hydrocarboxylation reaction, affording the desired product 8a in 76% yield at gram-scale . Then, methylation of 8a with MeLi resulted in the formation of nabumetone in 68% overall yield, providing a practical approach for scaling up photoreactions that involve reagents with low solubility (Figure ).…”
Section: Resultssupporting
confidence: 89%
“…To showcase the practicality of this method, we conducted a two-step gram-scale synthesis of anti-inflammatory drug nabumetone from commercially available 2-ethynyl-6-methoxynaphthalene ( 7w ) using our reductive hydrocarboxylation reaction. Given the poor solubility of oxalates in MeCN, a simple high-speed circulation flow was employed to scale up the photocatalytic reductive hydrocarboxylation reaction, affording the desired product 8a in 76% yield at gram-scale . Then, methylation of 8a with MeLi resulted in the formation of nabumetone in 68% overall yield, providing a practical approach for scaling up photoreactions that involve reagents with low solubility (Figure ).…”
Section: Resultssupporting
confidence: 89%
“…A segmented flow was observed through the flow of both the solution of reagents and gas (oxygen); finally, the coil photoreactor was subjected to LED irradiation (365 nm), resulting in 0.56 g of the desired product, with a high turnover frequency (835.2 µmol g −1 h −1 ). Recently, Wu and coworkers reported on a practical and very efficient approach to carry out photocatalyzed reactions in continuous flow by employing mpg-CN [73]. The authors demonstrated that switching from continuous flow mode to a high-speed circulation flow mode can strongly enhance productivity, allowing the photocatalyzed reaction mediated by solid-phase catalysts to be quickly scaled up.…”
Section: Carbon Nitridementioning
confidence: 99%
“…The nickel/mesoporous graphitic carbon nitride (mpg-CN) blended catalyst was selected for the photo-mediated ligand-free Buchwald−Hartwig C−N coupling reaction. A capillary photoreactor packed with nickel/mpg-CN was tested, with scarce results in terms of conversion and yield (12% Recently, Wu and coworkers reported on a practical and very efficient approach to carry out photocatalyzed reactions in continuous flow by employing mpg-CN [73]. The authors demonstrated that switching from continuous flow mode to a high-speed circulation flow mode can strongly enhance productivity, allowing the photocatalyzed reaction mediated by solid-phase catalysts to be quickly scaled up.…”
Section: Carbon Nitridementioning
confidence: 99%